Applied Aspects of Koshta and Agni in Panchakarma (International Journal of Ayurveda and Pharma Research, 2024)
Panchakarma is the elimination of Bahu dosha (excessive Doshas) in Bahu ati matra (excessive amount) through the Asanna marga (nearest route), thus all Panchakarma can be viewed under Poorvakarma (pre-operative), Pradhana karma (operative) and Paschat karma (post-operative). Koshta (bowel) and Agni play an important role in these stages. Koshta is the basic and important concept in Ayurveda. Koshta plays an important role in selection of the line of treatment. Koshta pariksha is necessary to evaluate the selection of Aushadha matra, Anupana, and Snehapana. Agni has great importance in maintaining good health. In clinical practice, Agni Pariksha (assessment of Agni) is very important, as only on this Pariksha, treatment plan can be decided. "Applied aspects" refer to the practical or real-world applications and implementations of knowledge, theories, principles, or research findings in various fields of study like Shalya Tantra, Shalakya Tantra, Kaumarabritya, Panchakarma and others. In the field of Panchakarma which includes anatomy, physiology, pathology, assessment and medicine. The medicinal aspect can be understood with the procedures followed in Panchakarma in terms of Poorva, Pradhana and Paschat karma. For Shodhana (purification Therapy) and Shamana (palliative), assessment and understanding of Koshta and Agni (fire) plays a major role.